Influence of rotor structure on cogging torque in a surface-mounted PM-generator - Greconici, Marian (JET on-line, 2019)
This paper deals with the analysis of the cogging torque in a surface-mounted permanent magnet generator in order to determine some techniques to minimize or eliminate the cogging torque. The simulation with finite element method (FEM) was carryout. A four-pole surface-mounted PM generator is investigated in the paper using FEM. The paper analyses the possibilities to reduce this type of torque by producing some asymmetry in the rotor structure. Two types of asymmetry were analysed: the PM pole arc with different widths, and the shifting of the PM. The numerical results obtained in the asymmetrical cases with symmetrical ones were compared and discussed. Finally, some conclusions are highlighted regarding the simulated results.
Keywords: cogging torque; electrical machines; električni stroji; FEM analysis; generatorji; metoda končnih elementov; rotorji; surface-mounted PM generator; trajni magneti